Portfolio of farm production and market risk management in agribusiness cooperatives of Paraná (Revista de Administração, 2011)
This paper shows an assessment of the practice of market risk management among cooperatives in the state of Paraná (Brazil) and a study of the agricultural production portfolio of this state, taking into account the risk-return relationship. Using the Markowitz model along with an E-V analysis, an efficiency boundary was determined in which it was possible to verify what portfolio changes would be required to achieve economic efficiency (defined here as the trade-off between risk and return). Through questionnaires and interviews, an analysis was conducted of the cooperatives' willingness to encourage such changes in their portfolios and in the production of their members. It was also possible to assess the degree of importance ascribed to sources of market risk and to a set of strategies that could be adopted to deal with these risks. The overall goal of this study was to evaluate what might be the influence of the cooperatives on changing production preferences, in order to improve the risk-return relationship. The authors found that the main motives that might affect production decisions are related to economic and rational aspects, such as the cooperative's strategic focus and the resistance of its members. Motives related to political or social aspects, intrinsic to the organizational characteristics of the cooperatives, do not have a substantial influence on the decisions about diversification as a management tool for the management of market risks within the Parana state context.